2016
DOI: 10.1589/jpts.28.2991
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between atherosclerosis and knee osteoarthritis as graded by radiography and ultrasonography in females

Abstract: [Purpose] The aim of this study was to assess the relationship between atherosclerosis and knee osteoarthritis grade in women as assessed by both ultrasonography and radiography. [Subjects and Methods] Seventy women diagnosed with knee osteoarthritis were classified into two groups according to cartilage grading/radiographic grading. Patients with Kellgren-Lawrence grades 1 and 2 were included in group 1, while those with Kellgren-Lawrence grades 3 and 4 were included in group 2. Patients with cartilage grades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…Also, in agreement with the findings of the present study, Ekim et al found that the duration of knee symptoms, WOMAC total and subscales scores were significantly higher in group with higher US grades than in group with lower US grades. Moreover, in agreement with our findings, the results of Ekim et al revealed that cIMT was directly correlated with the K-L grades and also with US cartilage thickness grades in patients with KOA [34].…”
Section: Ekim Et Al Also Divided the Koa Patientssupporting
confidence: 93%
See 1 more Smart Citation
“…Also, in agreement with the findings of the present study, Ekim et al found that the duration of knee symptoms, WOMAC total and subscales scores were significantly higher in group with higher US grades than in group with lower US grades. Moreover, in agreement with our findings, the results of Ekim et al revealed that cIMT was directly correlated with the K-L grades and also with US cartilage thickness grades in patients with KOA [34].…”
Section: Ekim Et Al Also Divided the Koa Patientssupporting
confidence: 93%
“…In addition, it is evidenced that OA patients are at an increased risk of mortality due to CVD [10]. In agreement with our findings, Ekim et al [34] found that the duration of knee symptoms, WOMAC total and subscales scores were significantly higher in group 2 (KOA patients with KL grade of 3 and 4) than in group 1 (KOA patients with grade 1 and 2).…”
Section: Regarding the Individual Components Ofsupporting
confidence: 92%
“…Cemeroglu et al 27 also reported a significant relationship between severe coronary stenosis and hand OA. An association between knee OA and the severity of AS was also suggested by Ekim et al 28 Few cohort studies have demonstrated that hand, knee, and hip OA are associated with AS. [29][30][31] An association between progression of OA and AS has been previously reported.…”
Section: Association Between As and Oamentioning
confidence: 53%
“…Several studies have postulated the possible association between OA and atherosclerosis. 10,13 While traditionally OA was considered to be a degenerative joint disorder, nowadays, it is being observed as a disorder that is highly correlated to the metabolic syndrome and chronic inflammation plays an important role in the pathogenesis of OA, as well as with other comorbidities like diabetes mellitus, hypertension, and cardiovascular disease. 28 Apart from its analgesic effects, acupuncture has been shown to exert anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…11 Oxidative stress, in which diet may also contribute to this condition, has a role with vascular pathogenesis and the progression of coronary heart disease (CHD). 12 Studies have also shown an association between atherosclerosis and OA, 13,14 and the suspected underlying mechanism is vascular alterations that cause a disruption in the circulation of the synovial membrane and subchondral bone, which leads to cartilage destruction. 10,15 Acupuncture, which is part of Traditional Chinese Medicine (TCM) treatment modalities, is commonly used in Asia, 16 and in recent years, its popularity has increased in Western countries.…”
Section: Introductionmentioning
confidence: 99%